The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1039/c3cp51973b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of a DOPA/ST monolayer on the Au(111) surface

Abstract: aIn order to study the influence of molecular structure on the formation of a monolayer, two molecules have been considered, namely N-stearoyldopamine (DOPA) and 4-stearyl-catechol (ST). The difference between these two molecules is the amide group in DOPA. By investigating these monolayers at different surface areas per molecule, the molecular configurations of a DOPA/ST monolayer on the Au(111) surface were obtained. We conclude that for both kinds of molecules, the p-interaction between the catechol group a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…[25,39] The energy required for aggregation (coalesces) is a much higher and negative surface charge on the particles is also very high and more energy is needed to overcome charge density on both of the particles colliding with each other. [40] As the reactor used in this research is conical in shape, and the flow is moving in only one direction. Therefore, the chance of collision of two particles with that high forces to attach can be assumed to be zero, and all the particles will move back into the bulk solution after the collision.…”
Section: Coalescesmentioning
confidence: 99%
“…[25,39] The energy required for aggregation (coalesces) is a much higher and negative surface charge on the particles is also very high and more energy is needed to overcome charge density on both of the particles colliding with each other. [40] As the reactor used in this research is conical in shape, and the flow is moving in only one direction. Therefore, the chance of collision of two particles with that high forces to attach can be assumed to be zero, and all the particles will move back into the bulk solution after the collision.…”
Section: Coalescesmentioning
confidence: 99%
“…The adhesion proteins secreted by marine mussels bind strongly to virtually all inorganic and organic surfaces in aqueous environments, accordingly serving as an intractable problem in the field of marine antifouling. , A common feature of such proteins is that they contain a high content of 3,4-dihydroxy- l -phenylalanine ( l -DOPA), which is considered to be responsible for their capacity to compete successfully with water at the surface and cross-link under water. , In the most recent decade, interaction mechanisms of DOPA side chains embedded in proteins and solid surfaces have been extensively studied, owing to a growing attraction in the respects of antifouling strategies and biomimetic adhesion. It can be concluded that DOPA plays an important part in the interactions through H-bonding, , coordination with metal/metal oxide, , or covalent cross-linking, , of which the detailed binding mechanisms of DOPA to different surfaces is an extremely important research topic, attracting great interests of scientists.…”
Section: Introductionmentioning
confidence: 99%
“…1B) are evaluated. 28,51 The position of the aromatic rings is described by the angle y. To characterize the degree of orientation and stretching of the aliphatic tails, a vector R e that contains the carbon atoms labelled from 1 to 18 as shown on the right-hand side of Fig.…”
Section: Structural Aspectsmentioning
confidence: 99%
“…The properties of DOPA and ST on a gold surface has been studied both experimentally and theoretically in our previous studies. 27,28 It has been known that the results of a molecular simulation containing water molecules can be influenced by the choice of the water model. 29,30 Thus, to assess the influence of water models, DOPA/ST monolayers on a water surface are simulated with two kinds of water models (TIP4P/2005 31 and SPC 32,33 ).…”
Section: Introductionmentioning
confidence: 99%